3 sonates pour piano dédiées au celèbre J. Haydn, par L. van Beethoven ... Oeuvre 2 ... No. [1] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; S. Richault; France, 2023)
Early edition of the Piano Sonata no. 1 in F minor, op. 2, no. 1, published in Paris by S. Richault.